Kecanduan Gawai Terhadap Cara Gaya Bersosialisasi - Buche Bukit Finjani; Harry Priatno; Yayang Fitri Fadilah (IHSA Institute, 2022)
This research is motivated by the increasing use of gadgets in the community, this research aims to describe how the influence of gadgets on social emotional development among adolescents to adults in Group 6 in Bandung precisely in the Binong area.The research method used is descriptive qualitative research. This research approach uses phenomenological methods. The samples in this study numbered 9 people, Based on the observations we have done in the area, the average use of gadgets in the area can be said to be quite high, of course with this we can get diverse and accurate information from informants in the area. Data retrieval techniques conducted are interviews, As for several categories of informants, namely students (16-18 years), teenagers or students (19-25 years) and the last there are parents (26-50 years). This shows that the use of gadgets has a positive influence of 30% and a negative influence of 70% on the development of addiction, social, emotional, adolescents and adults in group 6 in Bandung precisely in binong area. However, the influence is not significant.